THE ROLE OF BANK INDONESIA REPRESENTATION OF WEST KALIMANTAN IN REACHING TECHNOPRENEURSHIP: POLITICAL ECONOMIC PERSPECTIVE - Elyta, Elyta; Razak, A; Warjio, Warjio (CosmoGov: Jurnal Ilmu Pemerintahan, 2021)
Perspectives related to the political economy have links with state and economic issues. Political economy is focused on the role of the state in improving the welfare of its people. Based on this, this study aims to analyze the role of the state, Bank Indonesia, West Kalimantan Province in enhancing the wellbeing of MSMEs through technopreneurship. This research is motivated by a problem that is not yet comprehensive market coverage and promotion of MSME products; the low quality of products produced and the limited market network and marketing of MSME products; MSME managerial organization has not been organized; and minimal cyber capital and security. Based on these problems, Bank Indonesia of West Kalimantan Province has conducted production assistance, digital-based promotion, online marketing access, financial management, and organization of technopreneurship. This research uses mixed, qualitative, and quantitative research methods. Primary data were collected through questionnaires and interviews. The questionnaire was given to all respondents, namely all participants who took the financial technology incubator class program. Next, interviews were conducted with the Head of the Bank Indonesia Representative Office in West Kalimantan and the two best participants representing. Secondary data was taken using data from various articles and books related to financial technology. The results of the study explained that Bank Indonesia played a role in the formation of technopreneurship. Thanks to the role of Bank Indonesia, MSME production remains flexible despite being hit by global shocks.gb777